From Catastrophe to Cooperation : A Study of Disaster Diplomacy in Turkey's Earthquake Responses - Akbulut, Denizhan; Rolenc, Jan Martin, 1980-; Přikryl, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates the notion of disaster diplomacy by examining international relations and cooperation/antagonism before and after natural disasters comparatively between the 1999 İzmit Earthquake and the 2023 Kahramanmaraş Earthquake in Turkey. Next to the 1999 İzmit Earthquake, which also provided compelling case studies of disaster as a means of temporarily thawing geopolitical tensions, as evidenced by the rapprochement between Greece and Turkey, the 2023 Kahramanmaraş Earthquake demonstrated the evolution of disaster response mechanisms in a more interconnected and multilateral global context. It analyzes how state and non-state actors (such as NGOs, international organizations, and grassroots initiatives) engage in and manipulate disaster diplomacy. It also explores how technological progress — along with narratives that dominate the media — impacts the way aid is delivered, coordinated, and viewed by the public. From a constructivist perspective, the study highlights the socially constructed nature of disasters and the ability of disasters to reproduce and transform power relationships, norms, and identities in the context of international relations. Based on a thematic and comparative data analysis, this thesis learns continuity and change in disaster diplomacy, which not only enhances our understanding of limits and opportunities for disaster diplomacy but also has implications for cooperative peace-building in a turbulent, globalized world.
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses